The interpretation of groundwater data in groundwater modeling system - Abdul Muniem, Asmaa; Said, Salim (Universiti Putra Malaysia, 1999)
Groundwater modeling is a multidisciplinary science, involving proper interpretation of various groundwater data. If the groundwater in a point source pollution area is to be studied, one should know parameters such the hydrology, land use, soils, topography, hydrographs and maps of the region. The entire GMS (Groundwater Modeling System) system consists of graphical user interface (the GMS program) and a number of analysis codes (MODFLOW, MT3D, RT3D, MODPATH, SPEED2D, FEMWATER). The objective of this paper is to perform the groundwater simulation, using the MODFLOW - Grid and Conceptual Approach. The MODFLOW - Grid Approach involves working directly with the 3D grid and applying source/sinks and other model parameters on a cell by cell basis. The model handles discretization of space in horizontal direction by reading the number of rows, the number of column and the width of each row and column and vertical by specifying the layer thickness and hydraulic parameter. Flow between layers will be simulated by defining leakance values between aquifers. Flow into the system is due precipitation (recharge). Flow out the system due to discharging wells, drain and lake, which represented by a constant head boundary. The model which still to be developed can be used as useful tool to guide future field investigation. The result of this simulation can be used as flow filed for other GMS interface (like transport simulation - MODPATH) after using GIS tools (Geological Information System) in the map module.